Chonggu Granules Improve Cartilage Matrix Metabolism in Knee Osteoarthritis via the miR-148a-3p/Wnt/β-Catenin Pathway - Cheng L; Huang C; Li M; Shang S; Chen J; Tang Z (Dove Medical Press, 2023)
Lili Cheng,1 Chuanbing Huang,2 Ming Li,2 Shuangshuang Shang,2 Junjie Chen,1 Zhongfu Tang1 1The First Clinical Medical College, Anhui University of Traditional Chinese Medicine, Hefei, Anhui Province, 230038, People's Republic of China; 2Department of Rheumatology and Immunology, First Affiliated Hospital of Anhui University of Traditional Chinese Medicine, Hefei, Anhui Province, 230038, People's Republic of ChinaCorrespondence: Chuanbing Huang, Department of Rheumatology and Immunology, First Affiliated Hospital of Anhui University of Traditional Chinese Medicine, Hefei, Anhui Province, 230038, People's Republic of China, Tel +86-15156986428, Email Chuanbinh@163.comPurpose: This study aims to explore the effect and underlying mechanism of Chonggu Granules (CGG) in knee osteoarthritis (KOA) in rats.Methods: A papain-induced KOA model was established in rats. The pathological alterations of extracellular matrix in rat cartilage tissues were observed through hematoxylin and eosin (H&E) staining, followed by Mankin score for quantitative scoring. The ultrastructure of cartilage extracellular matrix was examined under a transmission electron microscopy (TEM). ELISA was used to measure the levels of IL-6, TNF-α, and IL-1β in rat serum. Immunofluorescence was performed for assessing the levels of MMP-3, MMP-13, and Col2al in rat cartilage. Western blot was used to identify the protein expressions of wnt1, GSK-3β, β-catenin, and Aggrecan in rat cartilage. The mRNA relative expressions of miR-148a-3p, wnt1, β-catenin, and GSK-3β in rat cartilage were detected by RT-PCR. Luciferase reporter gene was used to detect the target genes of miR-148a-3p.Results: CGG significantly improved articular cartilage tissue and extracellular matrix metabolism compared to the model group as indicated by H&E, Mankin score, and TEM data. Moreover, low, medium, and high doses of CGG reduced the levels of IL-6, TNF-α, IL-1β, MMP-3, and MMP-13 in serum to varying degrees but increased the levels of Col2al and Aggrecan. Mechanistically, CGG targeted wnt1 by increasing the expression of miR-148a-3p in a dose-dependent manner, thereby downregulating the mRNA and protein expressions of β-catenin in cartilage tissue and upregulating the mRNA and protein expressions of GSK-3β.Conclusion: CGG may control the miR-148a-3p/wnt/β-catenin signaling pathway to decrease the levels of its downstream target genes MMP-13 and MMP-3, increase the expressions of Col2al and Aggrecan, and downregulate the contents of inflammatory cytokines IL-6, TNF-α, and IL-1β, thereby improving the metabolism of cartilage extracellular matrix and alleviating the degeneration of articular cartilage in KOA.Keywords: knee osteoarthritis, cartilage extracellular matrix metabolism, chonggu granules, miR-148a-3p, Wnt/β-catenin signaling pathway